A model for knowledge management strategy : an application in real estate - Razali, Muhammad Najib; Juanil, David Martin; Othman, Siti Hajar (2006)
Real estate business nowadays has become a very and tight competitive. Thus, each of players in this business needs to shift to new paradigm of business. The base of organizational competitiveness in the contemporary economy has shifted from physical and tangible resource to knowledge creation. In engineering, knowledge management has become crucial part requires a profound insight into the task of engineers and their need of support. It is believe in real estate, knowledge management is important to find ways to use reuse and store knowledge as efficiently as possible. Real estate players need a large amount of reliable knowledge and information to ensure a successful of business. In addition, it involves the combination of various inputs in order to achieve an output or product. These developments offer opportunities for changes to organisational structures and the improvement of business process. The traditional approach of managing real estate business has proved to be too monolithic and lacking information for dealing with highly complex, multidimensional, and distributed systems. In the traditional paradigm little attempt is made in understanding how the information in real estate relates to other components or the effect that the information will have on the enterprise itself. This paper will try to explore a conceptual model to design knowledge management strategy especially to playa role in the way that one can capture, reason, represent, use for agreement between many stakeholders, competitors, customers and discover new information in industry to make betterment for industries.